Listing of the True and Practical Cyber Security Risks of Social Media: Why Is It a Dangerous Place For a Content Creator And a Business - Finska, Kia; Majanoja, Anne-Maarit; Hakkala, Antti (Germany, 2026)
This study focuses on the security risks of social media platforms from the perspective of an Social Media Influencer (SMI) or content creator. This study conducts interviews on SMIs and furthermore lists the risks of social media mentioned by the interviewees as well as found in literature. The risks are divided into three main themes: professional, technical and psychological. The conclusion of this study is that working with social media as an individual and with a brand is full of risks from all three themes. For an individual the professional risks cause the most worry, regarding subjects such as cancelling culture, brand image, too much responsibility for one individual, and customer satisfaction. The risks need to be recognized and worked on to ensure a safer working environment for the content creator. In the discussion, also the risks of social media work found in literature will be presented
Proceedings of the Annual Doctoral Symposium of Computer Science 2025 (TKTP 2025), Helsinki, Finland, June, 2025